Non-viral nano-immunotherapeutics targeting tumor microenvironmental immune cells. (October 2019) - Yong, Seok-Beom; Chung, Jee Young; Song, Yoonsung; Kim, Jaehyun; Ra, Sehee; Kim, Yong-Hee
Abstract: The tumor microenvironmental immune cells (TMICs) consists of myeloid cells (tumor-associated macrophages, dendritic cells, myeloid-derived suppressor cells, etc.) and lymphocytes (T cells and B cells), all of which could be immunologically suppressed through their interactions with cancer cells. Immunological understanding of the tumor microenvironment (TME) has led to great success in the development of clinical cancer immunotherapeutic. The most advanced cancer immunotherapies are chimeric antigen receptor-modified T cells (CAR-T cells) and checkpoint inhibiting antibodies blocking CTLA4, PD-1 and PD-L1. However, many hurdles remain that should be addressed for improved therapeutic efficacy and reduced side effects such as cytokine release syndrome and patient-death. In recent decades, nanoparticles have been demonstrated as an efficient drug delivery tool due to their ease of modification, biocompatibility and intrinsic tumor targeting effect, and also been applied for cancer immunotherapy. In this review, we briefly introduce the immunosuppressive functions of TMICs and review recent advances in the development of TMIC-targeted nanotherapeutics for cancer immunotherapy. Tumor-associated macrophage (TAM)-targeted systems have shown to deplete or repolarize macrophages to M1 state for anti-tumoral immune responses. Tumor-infiltrating T cell (TIT)-targeted strategies have provided the activation of effector T cells and suppression of regulatory T cells in tumor, overcoming the current hurdles of single regimen checkpoint inhibitors. Lastly, recent studies on dendritic cell-targeted mRNA vaccination are discussed and the future perspectives of nano-immunotherapeutic for next-generation of cancer immunotherapy is emphasized.